2019
DOI: 10.2169/internalmedicine.1923-18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combined Thrombomodulin and Antithrombin in Anticoagulant Therapy for Acute Cholangitis-induced Disseminated Intravascular Coagulation

Abstract: Objective The efficacy and safety of concomitant use of antithrombin (AT) with recombinant human soluble thrombomodulin (rTM) for acute cholangitis-induced disseminated intravascular coagulation (AC-induced DIC) remains unclear. This study was conducted to investigate the efficacy of AT combined with rTM as anticoagulant therapy for AC-induced DIC. Methods One hundred patients with AC-induced DIC received anticoagulant therapy using rTM from April 2010 to December 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…A selection may have caused bias in the endoscopic procedures, such as EST, stone removal, and the method of EBD, because the endoscopic procedures were left to the discretion of the attending endoscopist. Treatment outcomes may be affected by anticoagulant therapy and antibiotics [14,15,24,25]. Furthermore, this study used a retrospective design, and the number of patients was small because of the rare nature of the subject disease, thereby indicating that a large-scale, prospective study is necessary to confirm our findings.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A selection may have caused bias in the endoscopic procedures, such as EST, stone removal, and the method of EBD, because the endoscopic procedures were left to the discretion of the attending endoscopist. Treatment outcomes may be affected by anticoagulant therapy and antibiotics [14,15,24,25]. Furthermore, this study used a retrospective design, and the number of patients was small because of the rare nature of the subject disease, thereby indicating that a large-scale, prospective study is necessary to confirm our findings.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, treatment outcomes may be affected by anticoagulant therapy. However, only a few reports on anticoagulant therapy for AC-induced DIC exist [14,15,24,25], so very little evidence exists that can form a basis for the selection of anticoagulant agents for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the efficacy of AT supplementation in combination with rTM preparation in 2019 reported that the concomitant use of AT with rTM for acute cholangitis-induced DIC may not improve treatment outcomes. 22 A multicenter study evaluating the clinical effectiveness of rTM in 284 patients with acute cholangitis and sepsis-induced DIC who underwent biliary drainage 23 concluded that after propensity score matching, the 28-day survival rate was significantly higher in the rTM group when compared with the non-rTM group. Thus far, many reports have suggested the usefulness of rTM preparations in patients with septic DIC caused by biliary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few reports have evaluated the treatment of DIC caused by acute cholangitis. 11,12,20 Suetani et al 12 evaluated the role of rhTM in the treatment of DIC caused by acute cholangitis. Among the 66 patients evaluated (rhTM group, n = 36, non-rhTM group, n = 30), the DIC resolution rate on day 9 was statistically significantly higher in the rhTM group compared with the control group (83.3% vs 52.8%, P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…6 Recombinant thrombomodulin (rhTM) is available in Japan and is potentially effective in the treatment of DIC. 10 Several studies related to drugs for the treatment of acute cholangitis have shown negative results in improvement of overall survival (OS) with rhTM, 11,12 and the evidence in this field is still insufficient. However, as mentioned above, biliary drainage might be technically feasible in almost all patients.…”
Section: Introductionmentioning
confidence: 99%